The comparison score of SPEEDS, MEDS, SOFA, APACHE II, and SAPS II as predictor of sepsis mortality: A Systematic Review - Nova Maryani; Calcarina Fitriani Retno Wisudarti (Pelopor Publikasi Akademika, 2023)
We performed the comparison of characteristics and values under the curve, including Sepsis Patient Evaluation Emergency Department Score (SPEEDS), Mortality in Emergency Department Sepsis (MEDS), Sequential Organ Failure Assessment (SOFA), Acute Physiology and Chronic Health Evaluation II (APACHE II), and Simplified Acute Physiology Score (SAPS II). We searched PubMed, Science direct, ProQuest, and EBSCO for identify full-text English-language papers published between 2012-2022. We discovered that each of the five-scoring lead to mortality forecasts in sepsis patients. MEDS predicted mortality in sepsis patients better than SAPS II after 28 days but the SPEEDS was more accurate than MEDS. The SOFA score predicts mortality better than the APACHE II. APACHE II has lesser validity than SAPS II. The AUC SOFA scores have greater in diagnosing sepsis patients’ mortality than other scores. However, they are overstated, inefficient, and non-cost-effective, making SOFA scoring unfavourable in enhancing healthcare quality.